Does the family physicians’ characteristics affect Cervical Cancer Screening rates? - Sayed, Sayeeda Amber; Naugler, Christopher; Dickinson, James (International Journal of Population Data Science, 2018)
Introduction While the effectiveness of cervical cancer-screening (CCS) programs is well accepted, concern is growing regarding Family physicians (FP) poor adherence to CCS guidelines resulting in over and under screening. In Canada, it is a FP responsibility to ensure that the CCS is done as per guidelines and with appropriate follow-up. Objectives and Approach To identify primary care physicians’ characteristics that are associated with over and under CCS for eligible women in Calgary, Alberta. We accessed the Calgary Laboratory Services data for 1475 FPs practicing in Calgary and linked it with the Physicians database of College of Physicians and Surgeons Alberta database. We then matched FP’s gender, country and year of medical school graduation, years since medical school graduation, certification in family medicine and their clinic address with their CCS testing patterns. Using doctors as their own controls, we compared data from 2010-2016 to determine practice variations in CCS patterns subsequent to guideline changes. Results We analyzed approximately 2,400,000 Pap test requisitions (approx. 300,000 per year) to identify screening patterns from 2010-2016 of 1475 family practitioners practicing in Calgary. Our preliminary results identified significant variations in the test ordering patterns of FPs. Approx. half of the male FPs were not performing CCS tests on their eligible female patients. Female FPs ordered more CCS tests than their male counterparts. FP trained in North America, were ordering more pap tests than FPS trained elsewhere. Decreased CSS was also observed among FPs practicing in Northeast Calgary. Conclusion/Implications We detected three CCS patterns: FPs who never perform CSS on eligible female patients; FPs who followed recommended guidelines for performing CCS tests and FPs who performed CCS tests, not following the guidelines. To ensure appropriate use of CSS, identifying intention-behavior relationships and innovative educational interventions for FPs are required.